Study of structural changes in the territorial development of the republic of Tatarstan - S. G. Sternik; I. F. Gareev; A. M. Nasrutdinov (Vestnik MGSU)
Introduction. The concentration of population and economic activity in agglomerations is primarily due to comfortable living conditions and developed infrastructure. At the same time, the issues of housing development in recent years have gone beyond the discussion of the problems of development of the construction industry and have become the subject of spatial development research. Housing stock and infrastructure facilities in the periphery do not correspond to demographic and migration processes. Thus, there is a need to develop analytical tools capable of planning a balanced infrastructure of the region.Materials and methods. Two research methods were used to investigate the set tasks: 1) studying the dynamics of key indicators of the region’s development; 2) calculation of the value of indices reflecting the concentration of the studied indicator (Herfindahl – Hirschman index — for the volume of housing construction, population concentration and the number of jobs; concentration coefficient of economic activity indicators).Results. The analysis of the main factors has shown that the long-term growth of the share of the population older than working age occurs in parallel with the growth of the population younger than working age. This imbalance is certainly the achievement of the state’s priorities in the field of improving the quality of life of the population through the introduction of social support measures for elderly citizens and young families. In agglomerations, jobs are technological and productivity is higher. Residence in the metropolitan area is considered not only as a place of work but also as a comfortable place to live.Discussion and Conclusion. The study of the regions of the Republic of Tatarstan allowed to show a complex situation with spatial development of the region — concentration in agglomerations and destruction on the periphery. In this regard, the study of agglomeration processes should become one of the elements of the national regional policy.